Causality of genetically proxied immunophenotypes on cardiovascular diseases: a Mendelian randomization study - Wang, Xuehan; Cheng, Huixin; Feng, Meng; Jiang, Bing; Ren, Chunzhen; Chen, Qilin; Zhi, Xiaodong; Li, Yingdong (Frontiers in Immunology, 2024)
Background: Cardiovascular diseases (CVDs) stand as the foremost global cause of mortality, prompting a growing interest in using the potential of immune cells for heart injury treatment. This study aims to assess the causal association between immune cells and CVDs.: A total of 731 immune cells were derived from a previously published genome-wide association study (GWAS), which included approximately 22 million genetic variants among 3,757 individuals of Sardinian ancestry. Genetic associations with atrial fibrillation (AF), heart failure, coronary artery disease, myocardial infarction and stroke were extracted from large-scale GWAS. A two-sample Mendelian randomization (MR) analysis was used to assess the causal association between immune cells and CVDs. Replication MR analysis based on FinnGen dataset and meta-analysis are sequentially conducted to validate causal relationships.Results: Collectively, genetically predicted 4 immune cell traits were associated with AF and 5 immune cell traits were associated with stroke. Increased levels of IgD-CD38dim absolute count were associated with a higher susceptibility to AF, while increased expression of CD14+ CD16+ monocytes, CD62L on CD62L+ myeloid dendritic cells, and CD16 on CD14-CD16+ monocytes were linked to a decreased susceptibility to AF. Additionally, an elevated susceptibility to stroke was linked to an increase in the percentage of CD39+ resting Tregs and heightened CD27 expression on IgD-CD38+ cells. Conversely, a decreased susceptibility to stroke was associated with increased CD40 expression on monocytes, particularly on CD14+ CD16+ and CD14+ CD16-monocytes, with the latter two showing the most compelling evidence.This study identified several immune cell traits that have a causal relationship with CVDs, thus confirming that immune cells play an important role in the pathogenesis of these diseases.